Anti-PD-1 Therapy-Associated Perforating Colitis. (31st May 2018) - Celli, Romulo; Kluger, Harriet M.; Zhang, Xuchen
Abstract : Inhibition of immune checkpoint T cell regulatory molecules by using programmed cell death protein 1 (PD-1), or its ligand (PDL-1), and cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) has been increasingly used to treat advanced malignancies. The immune-related adverse effects associated with these treatments such as diarrhea, colitis, and CTLA-4 treatment-associated perforating colitis have been reported. However, anti-PD-1/PD-L1-associated perforating colitis has rarely been reported. We report a case of colonic perforation in a patient recently treated with pembrolizumab, a PD-1 inhibitor for metastatic melanoma. Awareness of anti-PD-1/PD-L1-associated colitis and perforation will facilitate a timely diagnosis and management as they are increasingly used in oncology.